Identification of Lexicon Forms in Texts that Have the Potential to Cause Conflict in the City of Surakarta in Digital Media (A Forensic Linguistic Analysis) - Wahyudi, Bagus; Suryadi, Muhammad (Proceedings International Conference of Culture and Sustainable Development; Vol 1 (2023): PROCEEDINGS ICOCAS, 2023)
This research aims to identify lexicon forms in conflict texts on digital media in Surakarta City. This research uses forensic linguistics approach by applying the theory of lexicon form based on word structure and category. The data collection method used in this research is the documentation method. The documentation method was conducted by reading, observing, and recording texts that have the potential to cause conflict in Surakarta City in digital media. Data analysis method is used to describe the lingual unit based on the structure of lexicon form by considering the aspects of topicalization of lexicon in the sentence. The results of this study suggest that lexicons that have the potential to cause conflict in Surakarta City in digital media have various forms. This study found several categories of data analysed with a forensic linguistic approach and references to the ITE Law and the Criminal Code. This study found two types of lexicon forms based on its structure, namely monomorphemic and polymorphic, as well as lexicon forms based on word categories. Lexicons that have the potential to cause conflict in digital media are dominated by lexicons with verb and adjective categories.Â